UPAYA KONSERVASI EKS-SITU FAMILI BEGONIACEAE DARI TAMAN NASIONAL BUKIT BARISAN SELATAN DI KEBUN RAYA LIWA, KABUPATEN LAMPUNG BARAT, PROVINSI LAMPUNG - Esti Munawaroh (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
Begoniaceae is one of the largest families in Angiospermae that has economic value, for ornamental plants and traditional medicine. In Bukit Barisan Selatan Nasional Park (TNBBS), there are many species of Begonia that are relatively abundant in population. Conservation efforts need to be done, due to the destruction of continuous forest areas that lead to reduced biodiversity of Begonia plant species. Exploration activities have been undertaken to collect the various species of Begoniaceae in TNBBS, and then planted in Liwa Botanical Garden located in Liwa, West Lampung. As a conservation effort several studies have been conducted to adapt some Begonia species. From the exploration results have been obtained 8 types of Begonia is Begonia atricha (Miq.) Miq. ex A.DC, B. areolata Miq., B.cf. bracteata, B. isoptera Dryand ex. Sm.B.cf. vuijekii Koord, B.cf. scottii Tebbit ,. B. lepida Blumedan B. muricata Blume.Keywords: Conservation, Begoniaceae, Liwa Botanical Garden